The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1007/s10620-018-5222-1
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Quality of Life, Work, and Activities Among Adults with Clostridium difficile Infection: A Multinational Survey

Abstract: BackgroundEvidence of humanistic detriments of Clostridium difficile infection (CDI) remains limited.AimsTo assess humanistic burden associated with CDI.MethodsSelf-reported National Health and Wellness Survey data between 2013 and 2016 were analyzed for the USA, five European countries, China, and Brazil. Outcome measures included SF-36v2® for health-related quality of life (HRQoL) and Work Productivity and Activity Impairment questionnaire. Respondents (≥ 18 years old) were classified as (1) currently treate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
43
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 32 publications
(27 reference statements)
2
43
0
Order By: Relevance
“…A larger difference in utility weights between healthy patients and patients with CDI would, therefore, lead to FMT being even more cost-effective than concluded in most of the studies. However, a multinational study by Heinrich et al [ 35 ] based on the 36-item Short Form Health Survey (SF-36) found a utility weight of 0.58 and 0.64 in patients with a current and previous CDI episode, respectively. This difference between CDI and “healthy” patients is smaller than the differences applied in most of the health economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…A larger difference in utility weights between healthy patients and patients with CDI would, therefore, lead to FMT being even more cost-effective than concluded in most of the studies. However, a multinational study by Heinrich et al [ 35 ] based on the 36-item Short Form Health Survey (SF-36) found a utility weight of 0.58 and 0.64 in patients with a current and previous CDI episode, respectively. This difference between CDI and “healthy” patients is smaller than the differences applied in most of the health economic evaluations.…”
Section: Discussionmentioning
confidence: 99%
“…Factors that contribute to higher CDI incidence in the elderly include changes in fecal microbiome, immune senescence, reduced gastric acid production, prolonged antibiotic use, and increased hospitalization and immobilization rates. The presentation of CDI is similar in older and younger adults, but older adults may have a greater impact on quality of life due to decreased mobility, visual impairment, dementia, and other comorbidities (Heinrich et al 2018). In the United States, almost half a million people develop CDI yearly, with about 20% having at least one recurrence and 5% die within 30 days after initial diagnosis (Lessa et al 2015).…”
Section: Clostridium Difficilementioning
confidence: 99%
“…They were performed on a limited number of patients (n = 15 and n = 24 respectively) and used a qualitative approach (interviews of patients with open-ended questions). In Heinrich et al [16], authors used the SF-36v2 (Short Form 36-item Health Survey, version 2), a generic patient-reported outcome measure quantifying health-related quality of life. More recently, in Barbut et al [17], the impact on patients was measured with the European Quality of life -5 Dimensions -3 Levels of severity (EQ-5D-3 L) a widely-used generic questionnaire.…”
Section: Introductionmentioning
confidence: 99%